ANALISIS IMPLEMENTASI PEMUNGUTAN PAJAK BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN (BPHTB) DI INDONESIA - Habibah Ramadhani Nasution; Arofiani Mutmainah; Dina Cheetah Khairiyah; Dini Vientiany (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
The handover of management of BPHTB to district/city governments began January 1 2011. Since then, BPHTB has become a source of original regional income (PAD) and the further regulated by the respective regional regulations (Perda). Regional governments have the authority to set rates, collection procedures, and provide reductions or exemptions from BPHTB under certain conditions in accordance with applicable regional regulations. This research will analyze and examine how the BPHTB collection law is implemented in the regions. This research uses a library research approach or library study, that carried out by collect and analyze information from various library sources such as books, scientific journals, scientific articles and other trusted sources. The collected data is then analyzed to identify and understand how BHPTB collection is implemented in the regions according to the original evidence of its implementation according to the attached journal. This research aims to provide conclusions about how BPHTB collection is implemented in the regions. The results of this research are: it is very unfortunate that the implementation of BPHTB collection in the regions can actually be categorized as "not good enough" based on the two journals analyzed.